2014
DOI: 10.3390/molecules19056524
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Hydrophilic Palladium(II) Complex as a Highly Efficient Catalyst for Room Temperature Aerobic Suzuki Coupling Reactions in Aqueous Media

Abstract: Abstract:A study on room temperature Suzuki cross-coupling in an aqueous medium was carried out using a simple hydrophilic palladium (II) complex, trans-PdCl 2 (NH 2 CH 2 COOH) 2 as catalyst in the presence of K 2 CO 3 in air. This approach with a comparatively inexpensive and hydrophilic catalyst, mild reaction condition and aqueous media exhibits excellent catalytic activity towards the Suzuki coupling of aryl bromides and arylboronic acids, and good yields were obtained in the Suzuki coupling of activated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…[19,20] 2.2.2 General procedure for synthesis of target compounds (3a-f) Water (3 ml) and butanol (3 ml) were added into a dried round-bottom flask (50 ml) containing fluoro-containing phenylboronic acid (1.2 mmol), aryl halide (1 mmol), trans-PdCl 2 (NH 2 CH 2 COOH) 2 (0.01 mmol) and NaOH (3 mmol). The mixture was stirred at room temperature under aerobic conditions for 5 h. Then the resulting solution was extracted with ethyl acetate (10 ml × 3).…”
Section: Preparation Of Catalyst Trans-pdcl 2 (Nh 2 Ch 2 Cooh)mentioning
confidence: 99%
“…[19,20] 2.2.2 General procedure for synthesis of target compounds (3a-f) Water (3 ml) and butanol (3 ml) were added into a dried round-bottom flask (50 ml) containing fluoro-containing phenylboronic acid (1.2 mmol), aryl halide (1 mmol), trans-PdCl 2 (NH 2 CH 2 COOH) 2 (0.01 mmol) and NaOH (3 mmol). The mixture was stirred at room temperature under aerobic conditions for 5 h. Then the resulting solution was extracted with ethyl acetate (10 ml × 3).…”
Section: Preparation Of Catalyst Trans-pdcl 2 (Nh 2 Ch 2 Cooh)mentioning
confidence: 99%
“…Remarkably, from environmental and economic perspectives, the interest in catalytic processes by recyclable metal-based catalysts in aqueous media is dramatically increased. 14 Along this line and in continuing of our The catalyst was synthesized by the method outlined in Scheme 2. As shown in Scheme 2, at first the amino groups on chitosan chains were reacted with furfural to form CS-Schiff-base.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a ppm level of PdCl 2 has been developed for the Suzuki-Miyaura coupling reaction and in this process high-pressure and high-temperature water is necessary in order to gain a high yield [21]. Amino acid complexes show good catalytic performance in C-C bond and C-N formation [18][19][20]22,23]. Previous work has shown that Pd(NH 2 CH 2 COOH) 2 Cl 2 can catalyze the cross-coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that Pd(NH 2 CH 2 COOH) 2 Cl 2 can catalyze the cross-coupling reaction. In order to obtain a high yield of the coupling products, 0.01-1 mol% Pd is necessary [23]. Hence, pipecolinic acid, a kind of amino acid, was chosen as a ligand for the Pd-catalyzed Suzuki-Miyaura coupling reaction at room temperature in water, and a ppm level of Pd was enough to gain a high yield.…”
Section: Introductionmentioning
confidence: 99%